The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1063/1.1575492
|View full text |Cite
|
Sign up to set email alerts
|

Optical amplification in bismuth-doped silica glass

Abstract: We demonstrated an amplification phenomenon in a bismuth-doped silica glass at 1.3 μm with 0.8-μm excitation. This luminescent material is a promising candidate for use as the core-fiber material of an optical amplifier at the natural zero-dispersion wavelength (1.3 μm) of silica glass fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
143
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(146 citation statements)
references
References 1 publication
3
143
0
Order By: Relevance
“…These values are larger than the reported results in Bi-doped silica glass. 17 The optical amplification with 77 nm bandwidth implies the GGAB glass can overcome the disadvantages of the present praseodymium-doped fluoride fiber amplifiers such as brittle and narrow amplification bandwidth ͑25 nm͒. 28,29 Furthermore, it is significant to point out that the amplification phenomenon at 1560 nm is also observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are larger than the reported results in Bi-doped silica glass. 17 The optical amplification with 77 nm bandwidth implies the GGAB glass can overcome the disadvantages of the present praseodymium-doped fluoride fiber amplifiers such as brittle and narrow amplification bandwidth ͑25 nm͒. 28,29 Furthermore, it is significant to point out that the amplification phenomenon at 1560 nm is also observed.…”
Section: Resultsmentioning
confidence: 99%
“…16 It is exciting that optical amplification and lasing operation were also realized at present. [17][18][19][20][21][22] Among the obtained results, an interesting phenomenon that was seldom observed in other active materials is the excitation wavelength sensitive luminescence, and the largest displacement of 200 nm was reported. 12 This special characteristic is significant since it offers the opportunity for realizing tunable and broadband lasers and amplifiers.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] A lot of subvalent bismuth polycations were known since the 1960s and the broadband NIR and even mid-infrared luminescence from Bi 5 3+ and Bi 8 2+ polycations have been discovered recently. [29][30][31][32][33] It is interesting that NIR luminescence has also been detected from the bismuth dimer anion (Bi 2 2À ) in the (K-crypt) 2 Bi 2 crystal phase. 34 It was also demonstrated that the univalent bismuth cation (Bi + ) is the NIR emitter in the ternary halide crystals KAlCl 4 , KMgCl 3 , RbPb 2 Cl 5 , and CsCdCl 3 , 14,17,18,35,36 where Bi + substitutes isomorphically for the large alkali cations.…”
Section: Introductionmentioning
confidence: 99%
“…34 It was also demonstrated that the univalent bismuth cation (Bi + ) is the NIR emitter in the ternary halide crystals KAlCl 4 , KMgCl 3 , RbPb 2 Cl 5 , and CsCdCl 3 , 14,17,18,35,36 where Bi + substitutes isomorphically for the large alkali cations. On the other hand, it seems that several different emitters contribute to the net NIR photoluminescence in Bi-doped SiO 2 and GeO 2 -based glasses. 37,38 To understand the origin of NIR photoluminescence in Bi-containing silicate and germanate glasses, the investigation of model SiO 2 or GeO 2 -based crystals doped with bismuth is highly desirable, since crystal hosts offer a more restrictive and structured environment for the possible bismuth-containing luminescent species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation